1981
DOI: 10.1111/j.1432-1033.1981.tb05306.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐Glycosylation of Yeast Proteins

Abstract: The enzyme transferring the oligosaccharide from D~lPP-(GlcNAc)z(Man)~(Glc)~ to asparagine residues of glycoproteins has been solubilized from yeast membranes by extraction with detergents. Enzyme activity was tested by measuring transfer of the glycosyl moiety from D~IPP-['~C]saccharides to the hexapeptide Tyr-AsnLeu-Thr-Ser-Val. The rate of transfer was linear for 20 min, with about 40 of dolichyl-diphosphate-bound radioactivity transferred to the peptide.The solubilized enzyme has been characterized as foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
2

Year Published

1987
1987
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(93 citation statements)
references
References 29 publications
(13 reference statements)
1
90
0
2
Order By: Relevance
“…Digitonin has been the detergent of choice of many researchers for the purification of the active OT complex (4,30,31), although others have reported purification of catalytically active OT complexes by use of detergents such as Nikkol and Nonidet P-40 (13,14,32). Although a comparative study of OT activity in various detergents has not been reported yet, digitonin seems to be an ideal detergent for the purification of the OT complex because we found that the digitonin-solubilized microsomal extract retains high OT activity even after storage for several days at 4°C (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Digitonin has been the detergent of choice of many researchers for the purification of the active OT complex (4,30,31), although others have reported purification of catalytically active OT complexes by use of detergents such as Nikkol and Nonidet P-40 (13,14,32). Although a comparative study of OT activity in various detergents has not been reported yet, digitonin seems to be an ideal detergent for the purification of the OT complex because we found that the digitonin-solubilized microsomal extract retains high OT activity even after storage for several days at 4°C (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…One other very important note is that glucose-starved cells produce truncated LLO intermediates, which are less favorable to OST compared to fully glucosylated donors (Gao et al, 2005;Kelleher et al, 2003;Turco et al, 1977). An accumulation of truncated LLO intermediates can result in the addition of premature N-glycans onto the nascent polypeptides at a low rate or leaving Asn residue completely empty (Jackson et al, 1989;Quellhorst et al, 1999;Sharma et al, 1981). Both premature N-glycans and hypoglycosylation may have an effect on the N-glycosylation profile of the final product, which will be investigated in the next experiments in this thesis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have showed that a broad spectrum of assembly intermediates (GlcNAc2-PP-Dol to Glc2Man9GlcNAc2-PP-Dol) can be utilized by OST in vitro and in vivo (Jackson et al, 1989;Sharma et al, 1981). However, the presence of glucose units in the completed N-glycosylation precursor, Glc3Man9GlcNAc2-P-P-Dol, is essential for an efficient transfer reaction, and being preferred by more than 20-fold over nonglucosylated oligosaccharide-PP-Dol in cell free assays (Ballou et al, 1986;Parodi, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Substrate Recognition and Glycopeptide Turnover at Active Site May Involve Allosteric Regulation It has been demonstrated that oligosaccharide chains of varying length (Glc 0 -2 Man 0 -9 GlcNAc 2 -PP-Dol) can serve as the donor substrate of OT in vivo (47) and in vitro (48). Because OT preferentially transfers the fully assembled donor substrate, Glc 3 Man 9 GlcNAc 2 -PPDol, to the nascent polypeptide chain in vivo, investigation of the kinetic differences between the various sized intermediates as substrates versus the fully assembled dolichol-linked oligosaccharide substrate would be expected to provide insight into the mechanism utilized by OT to monitor the donor substrate specificity.…”
Section: Minireview: Unraveling Mechanism Of Protein N-glycosylation mentioning
confidence: 99%